The Influence of Policy Implementation Service Standards, and Information Systems on User Satisfaction of the MELATI Application at Badan Pemeriksa Keuangan Republik Indonesia - Bunga Oktora Ws; Muh. Ilham; Karno Karno (Sean Institute, 2025)
The increase in the number of requests for IT services provided by the IT Bureau is not accompanied by an increase in user satisfaction of IT services, this is indicated by a decrease in the satisfaction index for IT services by several work units at the BPK. In order to increase user satisfaction with IT services, the Author is interested in conducting research on the Effect of Implementation of Service Standards and Information Systems Policies on User Satisfaction of the Melati Application at the Audit Board of the Republic of Indonesia. This study uses a quantitative method with primary data collection techniques by distributing questionnaires to 275 IT service users at the BPK Head Office. The collected data were processed using the Covariance Based - Structural Equation Model (CB-SEM) analysis technique using Smart-PLS software. The results of the study showed that user satisfaction of the MELATI application (Y) was influenced by the implementation of service standard policies (X1) and information systems (X2) by 67.5% and the remaining 32.5% was influenced by other variables not used in this study. The variable of IT service standard policy implementation (X1) has a large and significant effect on user satisfaction of MELATI application in BPK with a path coefficient value of 0.495, t-value of 8.378> t-table 1.96 and p-value of 0.000 <0.05. Information system (X2) has a large and significant effect on user satisfaction of MELATI application in BPK with a path coefficient value of 0.465 or 46.5%, t-value of 8.199> t-table 1.96, and p-value of 0.000 <0.05. Efforts that can be made by the BPK IT Bureau are to improve the implementation of service standard policies and information systems by increasing the quantity of resources, communication, evaluation and updating of IT service standard policies and SOPs and implementing a survey of IT service user satisfaction on the MELATI application.